Optimal redistributive taxation - Tuomala, Matti (Oxford scholarship online, 2016)
The book explains in depth the Mirrlees model itself and presents various extensions of it. One set of extensions considers changing the preferences for consumption and work: behavioural-economic modifications (such as positional externalities, prospect theory, paternalism, myopic behaviour and habit formation) but also heterogeneous work preferences (besides differences in earnings ability). Another set of modifications concerns the objective of the government. The book explains the differences in optimal redistributive tax systems when governments, instead of maximising social welfare, minimise poverty or maximise social welfare based on rank order or charitable conservatism social welfare functions. In all extensions, the book illustrates the main mechanisms using advanced numerical simulations.